Erratum to transcatheter valve-in-valve implantation versus reoperative conventional aortic valve replacement: a systematic review - Team, Editorial (Journal of Thoracic Disease, 2016)
In the article that appeared on Page E83–E93, Vol 8, No 1 (January 2016) Issue of the Journal of Thoracic Disease (1), there is an error of Kevin Phan’s degree as “BS, MD”. The degree should have been shown as “BSc(Adv)”.